P127 Disrupting the cartilage mechanostat: the role of the ciliary protein IFT88 in the adolescent growth plate. (23rd April 2022) - Chang, Emer; Coveney, Clarissa; Wann, Angus
Abstract: Background/Aims: As long bone elongation draws to a close, the cartilaginous growth plate begins to ossify in preparation of growth plate fusion. Previous embryonic developmental in vivo work has identified the crucial Parathyroid Hormone-related Protein-Indian hedgehog (PTHrP-Ihh) feedback loop that is responsible for the proliferation of chondrocytes at the epiphysis, whilst also allowing for the hypertrophic differentiation of chondrocytes before ossification at the diaphysis. Indian hedgehog signalling relies upon the microtubule-based organelle the primary cilium, as disruption to either results in similar musculoskeletal phenotypes. Here, we asked for the first time whether juvenile and adolescent primary cilia disruption affected chondrocyte differentiation in the growth plate. Methods: We used a chondrocyte-specific conditional knockout (AggrecanCreERT2; Ift88fl/fl, cKO) of a key primary ciliary protein (Ift88) administering tamoxifen at (4, 6, 8 weeks-of-age) to both cKO and control (Ift88fl/fl) animals, collecting two weeks later (6, 8, 10-weeks-of-age). Immunohistochemistry was performed using type X collagen (ColX), a specific marker of hypertrophic chondrocytes. Results: Deletion of IFT88 resulted in large bi-lateral cartilaginous regions filled with disorganised ColX positive hypertrophic chondrocytes, indicating failed ossification. Our results indicate that deletion of IFT88 does not impact hypertrophic differentiation, but disrupts ossification processes downstream at the chondro-osseous junction, such as matrix remodelling and angiogenesis, necessary for growth plate closure. Interestingly, this phenotype was observed only in the bi-lateral most loaded regions of the tibia whilst the middle was unaffected. Conclusion: This observation indicates that the primary cilium could be involved in transducing mechanically regulated biophysical and signalling cues in the adolescent growth plate. Disclosure: E. Chang: None. C. Coveney: None. A. Wann: None.